Removal Pollutants in Textile Wastewater Using Unmodified Rice Husk - Zulti Fifia; Setiadewi Nurul; Waluyo Agus; Susanti Evi (E3S Web of Conferences, 2024)
The goal of this study was to evaluate rice husks potential to decrease both organic and inorganic contaminants from textile effluent. Rice husks are added in amounts up to 38% of the total adsorption bed volume. Using a submerged flow system with a three-day HRT, the native textile effluent (diluted to 75%) was constantly pumped at a rate of 15 ml/minute. In-situ and laboratory analyses of the water quality parameters were conducted. The treated water by rice husk has met the requirements for river ecosystems with parameter values such as pH and Temperature is normal, TSS 65 mg/L, TDS 400mg/L, DO 4 mg/L, COD 200 mg/L, TN 5 mg/L, and TP 2 mg/L. TSS, COD, Ammonium, TP, and TN efficiency of removal were 86.94%, 84.19%, 67.25%, 61.24%, and 48.72%, respectively. The difference in removal efficiency can be attributed to various factors such as the nature of the pollutant, the adsorption capacity of the adsorbent, the concentration of the pollutant, and the interaction between the adsorbent and the pollutant. The wastewater treatment with rice husk is a promising approach for industrial-scale applications due to its adsorption properties and cost-effectiveness.